Purchasing Behaviour of Farmers for Bio-Fungicide in Meerut District of Uttar Pradesh - Aparna Singh,; Satyveer Singh Meena,; Vikash, (Indian Journal of Extension Education, 2023)
In this study, an attempt was made to examine the variables affecting farmers' satisfaction with bio-fungicide use, the variables affecting their buying behaviour for the product, and the constraints faced by the farmers in the usage of bio-fungicides. A total of 100 farmers were selected on the basis of snowball sampling. RBQ mean was calculated to find out the most influencing factors for purchasing of bio fungicide by the farmers. Garrett's standard procedure was adopted to determine the significance of a number of different factors as expressed by respondents in the use of bio-fungicides. It was found that the retailers' influence, quality, price of positives, and the opinion leaders with implant agency were the important factors that affect the purchasing decision of farmers. Further, a substantial percentage of farmers in the research area were quite satisfied with the bio-fungicide's efficacy, followed by its relative quality and history of widespread usage.